Systemic diseases in patients with central retinal artery occlusion or its branches in the material of Department of Ophthalmology of Medical University of Lublin - Matysik, Anna; Gerkowicz, Marek; Lewandowska-Furmanik, Maria (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Patients with central retinal artery occlusion usually suffer from serious systemic diseases that could be potentially threatening life. Retinal emboli are associated with the presence of hypertension and other cardiovascular diseases, diabetes mellitus, hematological disturbances or infections. The goal of this study is the assessment of the most common coexisting systemic diseases in patients with the occlusion of retinal arteries. We retrospectively studied 51 patients with symptomatic retinal artery occlusion treated in The Department of Ophthalmology, Medical University of Lublin from 1990 to 2003. The most common concomitant diseases were hypertension, cardiovascular diseases and brain stroke. Eight of 51 patients died. The most frequent reason of death was cerebral stroke. Cardiovascular and cerebovascular examinations should be recommended for patients with retinal emboli.